Effect of different irradiation dose treatment on the lipid oxidation, instrumental color and volatiles of fresh pork and their changes during storage. (June 2017) - Li, Chengliang; He, Lichao; Jin, Guofeng; Ma, Sumin; Wu, Wenmin; Gai, Lan
Abstract: This study mainly investigated the effect of different doses irradiation (0, 3, 5 or 7 kGy) on the quality changes of pork during 4 °C storage by determining the irradiation off-odor intensity, thiobarbituric acid reactive substances (TBARs), fatty acid composition, volatiles and color of the samples during whole storage. The results showed that ≥ 7 kGy irradiation could make the samples produce obvious irradiation off-odor. However, after 7 days storage irradiation off-odor was reduced. Lipid oxidation was also promoted by irradiation. Benzyl methyl sulfide was produced newly and significantly increased ( P < 0.05) by irradiation. Fatty acids in pork samples decreased significantly with irradiation dose increase within the range of < 7 kGy, but significantly increased ( P < 0.05) in samples of 7 kGy. Irradiation significantly increased the a* values regardless of storage time but had little effects on b* and L* values, and the increase of a* values was dose-dependent.